TANGGUNGJAWAB PELAKU USAHA DALAM MEMPERDAGANGKAN PRODUK SUSU SGM KADALUWARSA ( STUDI KASUS PUTUSAN PENGADILAN TINGGI PEKAN BARU NOMOR 264/PID.SUS/2015/PT.PBR ) - Alex Siswanto; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Tarumanagara, 2020)
Consumer rights are regulated Law No. 8 of 1999 concerning Consumer Protection of the Republic of Indonesia, one of which is the right to comfort, security and safety in consuming goods and / or services. This study aims to determine the responsibility of entrepreneurs who trade expired food. Therefore, consumer rights must be protected so that a sense of security arises in society. Consumer protection is a serious concern for authorized agencies so that expired products are not spread and cause fatalities. This research examines how the responsibility for actors trading expired products and the application of consumer protection laws and related laws such as the Food Law and Health Act. To support this research the authors used data collection techniques in the form of interviews and literature studies. The results of this study conclude that the application of consumer protection laws and other laws related to food have not been implemented properly, where business actors as providers of goods and services do not pay attention to their obligations as business actors and consumer rights protection. Problems or constraints in the application of consumer protection enforcement both the issue of expired food or other consumer disputes, namely the authorized agency. This can be seen from the regulations governing this case that there are many and complete both in private law and public law, but everything is returned to the agencies that apply the consumer protection law.